A CROSS-SECTIONAL STUDY CONDUCTED FOR THE ASSESSMENT OF PREMENSTRUAL SYMPTOMS AMONG THE ADOLESCENT SCHOOL GIRLS OF MEHSANA CITY - PRIYANKA R PARMAR; SHRIKALP S DESHPANDE (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The ojective is to study menstrual patterns. To study the prevalence of pre-menstrual symptoms among high school girls. Methods: It is a cross-sectional, observational, and prospective study. A total of 384 adolescent girls were randomly enrolled in the study as per inclusion and exclusion criteria. Girls were belonging to higher secondary standards. Confidentiality was assured, and written informed consent was obtained. A data collection form was formed to conduct the survey. Ethical approval was obtained. The data were analyzed in MS Excel 2019. A descriptive analysis was done. Results: A total of 384 high school girls with an age of 15.65±1.16 years were enrolled in the study. The calculated mean body mass index (BMI) was 18.82±2.93. 40.4% had an underweight BMI. The majority of the adolescent girls had regular menstrual cycles, and a few had irregular menstrual cycles every month. More than half (60.41%) did not know about premenstrual syndrome. Physical premenstrual symptoms were a downward dragging sensation (58.78%), lower back pain (55.53%), acne flare-ups (44.63%), diffuse headaches (37.72%), and painful periods (33.88%). Psychological symptoms in hierarchy are anger or irritability (52.16%), less interest in usual activities (44.03%), pelvic cramping (45%), cravings for sweets (42.88%), and mood swings (41.53%). Conclusion: The prevalence of premenstrual symptoms was higher for physical and psychological symptoms. Physical symptoms can affect routine activities, and psychological symptoms affect girls’ behavior and mental status.